Implementasi Prinsip Demokrasi dalam Sistem Hukum Tata Negara - Frans Samuel Junero Butarbutar; Irwan Triadi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Democracy is an important component in state life, originating from the Ancient Greek words, namely demos and kratos. Democracy means absolute rule by the people, and means a government where all the people are governed by their representatives. The principle of democracy in the constitutional law system is an important foundation in building a fair, just and civilized society. The principle of democracy ensures active participation of all citizens in the formation and implementation of laws. In the context of constitutional law, this means the separation of powers between the executive, legislative and judiciary, as well as an effective monitoring mechanism for each branch of power. The principle of checks and balances is key in preventing abuse of power and ensuring that decisions taken reflect the interests of society at large. Democratic principles encourage inclusion and fair representation in legal drafting. Indonesia is a democratic country that has a strong constitutional framework, stipulated in the 1945 Constitution. Unfortunately, Indonesia is still classified as a country that is